Implementasi Model PBL-Pedati dalam Upaya Meningkatkan Kualitas Pembelajaran Diklat Kewirausahaan Sosial - Sunanik, Sunanik (JOEAI (Journal of Education and Instruction), 2021)
This study aims to improve the learning quality of Social Entrepreneurship Training by using the PBL-PEDATI model. An indicator of the increased quality of education and training is the increase in higher order thinking skills (HOTS) of training participants. The research method is "Classroom Action Research", the research subjects of the training participants are 20 participants. Data collection techniques are observation, interviews, and tests, descriptive statistical data analysis techniques. The results showed that there was an increase in the average score of tasks from the average score of 3.09 on task 1 which increased on task 2 to an average score of 3.47. In conclusion, the application of the PBL-PEDATI model in social entrepreneurship training can improve the higher-order thinking skills of the training participants. Suggestions to future researchers to implement the PBL-PEDATI model in courses that invite training participants to think analytically, critically, and creatively. Keywords: Learning Quality, HOTS, PBL-PEDATI Model.